A Simple Method to Improve Smoke Exhaust Effectiveness of a Shallow-buried Urban Tunnel Fire with Natural Ventilation. Issue 3 (17th February 2021) - Fan, Chuangang; Chen, Jian; Zhou, Yang; Li, Linjie; Zhang, Jiaqing; Fan, Minghao; Liu, Xiaoping
ABSTRACT: In order to improve the natural ventilation performance of a shallow-buried urban tunnel under the influence of external wind blowing above the shaft, a new method with installing a jet fan downstream of the shaft was proposed and a set of simulations were conducted to validate its effectiveness. The detailed smoke spread characteristics, such as mass flow rate, temperature, and velocity vector, were analyzed together with varying the ambient wind speed above the shaft, the longitudinal wind speed in the tunnel, and the velocity of the jet fan. Results show that under the coupled push effect of the longitudinal wind upstream of the fire and the airflow of jet fan downstream of the shaft, the block effect of the strong ambient wind on the vertical flow of smoke through the shaft can be overcome completely. In the tunnel, almost all the fire-induced smoke is confined between the fire and the shaft, and smoke can only be exhausted from the shaft. The findings can be a reference for tunnel ventilation design.